Answer:
-2 - 2i
Explanation:
Complex number
Add the real numbers (1 and (-3) ) and add the complex numbers [ 4i and (-6i) ]
(1 - 6i) - ( 3 - 4i) = 1 - 6i - 3 + 4i
= 1 -3 - 6i + 4i
= -2 - 2i
- We have to open the brackets. To do that Multiply (-1) with (-3) & 4i.
- Now, complex numbers are (-6i) and 4i. So combine them. 6i and 4i have different signs. So, subtract and the result will have bigger number sign. Here the bigger number sign is negative. So, -6i + 4 i = -2i
- Now combine real numbers. 1 - 3 = -2